An Automatic Streetlight System for Energy Saving - Rahimi, Nur Athirah Wannie; Md Nor, Danial (Evolution in Electrical and Electronic Engineering, 2023)
This paper presents as an implementing of a smart streetlight system has become an important feature of modern urban design, especially for improving traffic safety and lowering energy usage. The purpose of this work is to introduce a smart streetlight system that uses PIR and LDR sensors to detect vehicle and pedestrian activity and adjust the brightness of the streetlights accordingly. The system is controlled by the WeMos D1 R32 microcontroller, which enables real-time monitoring of the streetlights and effective energy management. In addition to these functions, the smart streetlight system has an innovative alerting system based on Telegram. The technology is meant to automatically send a notification to maintenance support in the event of a damaged lamp, allowing them to take rapid action to fix the broken lamp. This not only improves the general administration of the streetlight system, but it also assures the safety of citizens by providing appropriate lighting on the streets. The findings show that the smart streetlight system may greatly reduce energy usage by shutting off the lighting when no motion is detected. Overall, the system is a dependable and cost-effective solution that can improve urban road safety and sustainability.